The efficacy of repetitive transcranial magnetic stimulation in postherpetic neuralgia: a meta-analysis of randomized controlled trials - Dai, Qi; Xu, Aihua; Wang, Kunpeng; Yang, Yang; Shao, Yang; Sun, Yongxin (Frontiers in Neurology, 2024)
Purpose: This systematic review and meta-analysis aimed to evaluate the efficacy of repetitive transcranial magnetic stimulation (rTMS) in postherpetic neuralgia (PHN). Methods: Through an extensive search in four databases until October 2023, we selected five randomized controlled trials adhering to our specific criteria, involving 257 patients in total. For continuous outcomes, the standardized mean difference (SMD) was calculated. Heterogeneity among the studies was assessed using Cochran’s I² and Q statistics, adopting a random-effects model for I² values over 50%. For assessing potential publication bias, we utilized both funnel plot and Egger’s test. Results: Our analysis found that rTMS reduced the overall visual analogue scale (VAS)(SMD: -1.52, 95% CI: -2.81 to -0.23, P=0.02), VAS at 1 month post-treatment (SMD: -2.21, 95% CI: -4.31 to -0.10, P=0.04), VAS at 3 months post-treatment (SMD: -1.51, 95% CI: -2.81 to -0.22, P=0.02), as well as patients' global impression of change scale (PGIC)(SMD: -1.48, 95% CI: -2.87 to -0.09, P=0.04) and short-form McGill pain questionnaire (SF-MPQ)(SMD: -1.25, 95% CI: -2.41 to -0.09, P=0.03) compared to the sham-rTMS group. Conclusions: Our study suggests that rTMS might have a potential alleviating effect on PHN symptoms. However, due to the limited number of studies and variations in rTMS parameters, larger sample studies involving more diverse populations, as well as further clarification of the most appropriate stimulation protocol, are still needed.